2018
DOI: 10.56536/ijmres.v8i1.39
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of behavioural biases on Investment Decision Making: A Moderating Role of Religiosity among Pakistani Investors

Abstract: This research study evaluated the extent to which psychological factors (overconfidence, confirmation bias) effect on investor’s decision-making process. The ultimate objective of the current study is to investigate the effect of psychological factors on investor investment decision making. To achieve this objective, this study used quantitative approach and cross-sectional research design. Survey was used to collect the data. Questionnaires were distributed among the individual investors and brokers of stock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Thus, the study supports the first hypothesis. As far as religiosity is concerned (p> 0.05= .761) which suggests that religiosity doesn't have any significant relationship with investors decisions, further interaction between overconfidence and religiosity is also insignificant (p>0.05=0.0672), results are consistent with Brimble et al, (2013), , Bailey and Sood (1993) and Mokhlis (2009) while it contradicts with Waseem et al, (2018). The study also concluded that risk perception has a significant impact on investor decision (p<0.05=0.00) in regression analysis results are consistent with Simon, Houghton & Aquino (1999), whereas Interaction between overconfidence and risk perception is insignificant (p>0.05=0.5072).…”
Section: Referencesmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, the study supports the first hypothesis. As far as religiosity is concerned (p> 0.05= .761) which suggests that religiosity doesn't have any significant relationship with investors decisions, further interaction between overconfidence and religiosity is also insignificant (p>0.05=0.0672), results are consistent with Brimble et al, (2013), , Bailey and Sood (1993) and Mokhlis (2009) while it contradicts with Waseem et al, (2018). The study also concluded that risk perception has a significant impact on investor decision (p<0.05=0.00) in regression analysis results are consistent with Simon, Houghton & Aquino (1999), whereas Interaction between overconfidence and risk perception is insignificant (p>0.05=0.5072).…”
Section: Referencesmentioning
confidence: 80%
“…The questionnaire comprises 5 sections where section 1 consists of demographic variables, which are gender, level of education, management, marital status, and age. Whereas section two depicts 7 item scale of Overconfidence which was developed by (Simon et al 1999), section three consist of 5 item scale of Religiosity developed by (Waseem et al 2018) Section four consists of 14 item scale of Risk perception which was developed by Simon et al (1999), lastly, fifth section consist of 6 item scale Investor's Investment decisions which was developed by Simon et al (1999). Bounded rationality, humans only process imperfect information quickly when it compares with the standard paradigm of reality (Lipman, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faith and religiosity play an important role in investors' intention to invest in SRI. Hameed et al (2018) found that religiosity has a moderating effect between psychological factors and investors' investment decisions. Religiosity reduces the negative effect of overconfidence on investors' investment and strengthens the positive relationship of confirmation bias on investors' investment decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Religious religiosity is a factor affecting an investor's decision-making process other than personality and risk preferences (Hameed et al, 2018). Religiosity plays an important role in making decisions about risky attitudes.…”
Section: Introductionmentioning
confidence: 99%